Pengetahuan Ibu tentang Pemberian Imunisasi di Desa Rumpa Kecamatan Mapilli Kabupaten Polewali Mandar - Darmiati, Darmiati; Arfan, Fatmin; Hamsah, Idawati Ambo; Syamsiah, Endang (Yayasan Mandar Indonesia, 2023)
Immunization is one way to actively increase a person's immunity against antigens so that when they are exposed to similar antigens, disease will not occur. The high infant and under-five mortality rate in Indonesia causes a decline in the degree of public health, one of the efforts to overcome this problem is the complete basic immunization program for infants and toddlers. The type of research used is descriptive research method. This research method is a study conducted to describe or describe phenomena that occur in society. This research aims to describe the mother's knowledge about basic immunization at the age of 0-12 months in Rumpa village, Mapilli sub-district. The results of the study showed that most of the respondents had very good knowledge, 50% (15 respondents), but those who had sufficient knowledge, 33% (10 respondents), and had less knowledge, 17% (5 people). Factors that support the knowledge of respondents is the level of education of respondents is the average level of education of respondents SMK/equivalent 50%, SMP 33%, and SD 17%.